Molecular characterization of fossil and extant dammar resin extracts: Insights into diagenetic fate of sesqui- and triterpenoids - Mallick, M.; Dutta, S.; Greenwood, Paul (2014)
The composition of sesquiterpenoids and triterpenoids in the solvent extract of extant, Miocene and Eocene dammar (i.e., Class II) resins has been determined and compared to investigate the vulnerability of these biomarkers to diagenesis. Molecular evidence (e.g., absence of bicadinanes) and low Rock-Eval maturity values (Tmax<400°C) of the fossil resins indicate that they have not yet reached the catagenetic stage. Significant changes in the sesquiterpenoid composition of the fossilised compared to the modern dammars were evident, whereas the triterpenoid products reflected only minor differences. The major sesquiterpenoids in the extant resin are the essential oil components, a-copaene, ß-bourbonene, ß-elemene, ß-caryophyllene, germacrene D, germacrene B and spathulenol. In contrast, the major sesquiterpenoids in the fossilised resins were C15 cadalene-based compounds such as dihydro-ar-curcumene, d-selinene, a-muurolene, calamenene, 5,6,7,8-tetrahydrocadalene and cadalene. This difference indicates the susceptibility of the essential oils and the transformation of germacrene D and cadinenes to cadalene-based compounds (e.g. calamenene and 5,6,7,8-tetrahydrocadalene, cadalene) during diagenesis. The triterpenoid assemblages in both fossil and extant resins were very similar with abundant ß- and a-amyrin in all resins. It was evident that ß-amyrin was more prone to diagenesis than a-amyrin. The terpenoid compositions of the fossil resins (cf. extant resin) clearly reveal the greater susceptibility of sesquiterpenoids to diagenetic alteration than pentacyclic triterpenoids. © 2013.